Reinterpreting the Ngembah Manuk Mbur Tradition as a Foundation for Child-Friendly Education in the Context of Karo Community - Br Sembiring, Maria Sinta; Hattu, Justitia Vox Dei (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Attention given to children from the womb plays a vital role in supporting their physical and character development. The Karo tribe has a seven-month pregnancy tradition called ngembah manuk mbur, which aims to provide care and attention to pregnant mothers and their unborn children. However, this tradition remains limited in terms of fulfilling the rights of unborn children. Therefore, this study aims to reinterpret such tradition in the light of a biblical-theological context and within the framework of a Child-Friendly Church that it can serve as a foundation for child-friendly Christian education in the context of Karo community. The study employs a qualitative method with a literature review to explore the concept of the ngembah manuk mbur tradition and the concept of a Child-Friendly Church. These concepts serve as analytical tools to examine the implementation of such tradition. The findings indicate that reconstructing the tradition based on biblical-pedagogical principles and within the framework of a Child-Friendly Church can transform it into a foundation for child-friendly education within the Karo community. Traditionally, ngembah manuk mbur is conducted to strengthen pregnant mothers and is only performed for first-born children. This study proposes three key reconstructions of the tradition: it should be performed for all children, it should be carried out throughout the mother's pregnancy, and it should serve as a way for all family members to welcome the child into the family.